Decision Support System for Car Selection with Fuzzy Analytical Hierarchy Process (F-AHP) on Auto2000 Kenjeran Surabaya to Minimize Service Time - Setyaji, Andrean Ricky; Sunarto, Dewiyani; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
Auto2000 Kenjeran Surabaya is one of the authorized dealers that operate as a sales, repair, maintenance, and supplier service network for Toyota parts. Location Kenjeran Auto2000 is located on Jalan Kenjeran No.516, Surabaya City, East Java. The process of buying a car on Auto2000 Kenjeran is carried out when the customer comes to the Kenjeran Auto2000 dealer or online via social media. When making the purchase process, sometimes customers are confused about choosing a car due to a lack of information about the car, besides that there are also new salesmen who find it difficult to know what the customer wants, making the service process that initially takes Â± 30 minutes to offer and provide information about the car can be Â± 45 minutes due to finding out what car the customer wants.Based on the existing problems, a solution is proposed for the Auto2000 Kenjeran in the form of a car selection decision support system using the fuzzy analytical hierarchy process method that can help customers find a car, because there is a car finder feature that can help customers find a car according to customer preferences by simply selecting and give a score for each criterion and the desired alternative, and the car results will come out immediately. In addition, there are also vehicles and recommendation car features that provide information about cars to customers.Based on the test results, there are several features in the application that can provide information about cars, make car reservations, and can search for cars according to the criteria and alternatives that have been provided, besides that the application can print car order data reports. So it can be concluded that the application is in accordance with the functions and needs of the user.